Proteasome-mediated cleavage of the Y-box-binding protein 1 is linked to DNA-damage stress response - Sorokin, Alexey V (2005)
YB-1 is a DNA/RNA-binding nucleocytoplasmic shuttling protein whose regulatory effect on many DNA- and RNA-dependent events is determined by its localization in the cell. Distribution of YB-1 between the nucleus and the cytoplasm is known to be dependent on nuclear targeting and cytoplasmic retention signals located within the C-terminal portion of YB-1. Here, we report that YB-1 undergoes a specific proteolytic cleavage by the 20S proteasome, which splits off the C-terminal 105-amino-acid-long YB-1 fragment containing a cytoplasmic retention signal. Cleavage of YB-1 by the 20S proteasome in vitro appears to be ubiquitin- and ATP-independent, and is abolished by the association of YB-1 with messenger RNA. We also found that genotoxic stress triggers a proteasome-mediated cleavage of YB-1 in vivo and leads to accumulation of the truncated protein in nuclei of stressed cells. Endoproteolytic activity of the proteasome may therefore play an important role in regulating YB-1 functioning, especially under certain stress conditions.